Oil refinery model : approach for a study of oil policy analysis in Thailand - Jarasphan Phumpuang; Zhai Youg-Ping; Bo, Khin; Surapong Chiraratananon; The Commission of the European Communities (Bangkok : Asian Institute of Technology, 1991)
The issue of energy policy in the prospects of reducing dependence on imported petrol e um products is of significant interest to policy makers and planners. Thus an analysis of oil policy is of considerable interest from energy policy and planning point of view. The basic purpose of this study is to establish oil refinery model in order to use as a tool for analysing oil policy. Linear programming is the methodology to optimize the refinery ' s profit level at the given various conditions. Oil refinery mode l are used for the analysis of ex-refinery price for petroleum products , the expansion of oil refinery capacity and environmental policy related with oil matter. The results show that the deregulation o f ex-refinery price for petroleum products should be proceeded when the local oil products are sufficient f or the total requirements. The expansion of refinery capacities are found to be urgently carried out considering the growth of oil products demand during the Seventh plan (1992-1996). The capability of existing facilities in oil refinery to produce unleaded gasoline are also studied and to found that, based on ex is ting facilities , the refining cost of unleaded gasoline is very high comparing with the imported price .
A Thesis submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science, School of Environmental, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Petroleum refineries -- Thailand